THE ROLE OF ARTIFICIAL INTELLIGENCE IN LANGUAGE TRANSLATION AND LINGUISTIC ANALYSIS - Rustamova Sadoqat (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
Artificial Intelligence (AI) has revolutionized language translation and linguistic analysis, significantly improving accuracy, speed, and accessibility. This paper explores the transformative role of AI-driven tools such as neural machine translation systems, natural language processing algorithms, and sentiment analysis models. By examining the underlying mechanisms, including deep learning and neural networks, the study highlights how AI enables real-time translation, context-aware analysis, and multilingual communication.